2022
DOI: 10.3389/fnagi.2022.919859
|View full text |Cite
|
Sign up to set email alerts
|

Convergent functional changes of the episodic memory impairment in mild cognitive impairment: An ALE meta-analysis

Abstract: BackgroundMild cognitive impairment (MCI) is considered to be an intermediate stage between normal aging and Alzheimer's disease (AD). The earliest and most common symptom of MCI is impaired episodic memory. When episodic memory is impaired in MCI patients, specific functional changes occur in related brain areas. However, there is currently a lack of a unified conclusion on this change. Therefore, the purpose of this meta-analysis is to find MRI-specific functional changes in episodic memory in MCI patients.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…MTG is a highly involved brain region in the language network and is thought to play a role in language‐related tasks (Briggs et al., 2021 ). It has been shown that functional impairment of the temporal lobe can be compensated by increased connectivity of the frontal cortical compensation network in MCI patients, thereby maintaining the cognitive status of aMCI patients, which is consistent with our results (Liang et al., 2022 ; Zhao et al., 2014 ). In our study, the left MFG showed an increase in FC.…”
Section: Discussionsupporting
confidence: 93%
“…MTG is a highly involved brain region in the language network and is thought to play a role in language‐related tasks (Briggs et al., 2021 ). It has been shown that functional impairment of the temporal lobe can be compensated by increased connectivity of the frontal cortical compensation network in MCI patients, thereby maintaining the cognitive status of aMCI patients, which is consistent with our results (Liang et al., 2022 ; Zhao et al., 2014 ). In our study, the left MFG showed an increase in FC.…”
Section: Discussionsupporting
confidence: 93%
“…During aging, episodic memory declines and has been suggested to be the most age-sensitive memory system [26]. A worsening in episodic memory is one of the earliest and most common symptoms of mild cognitive impairment, and in people with Alzheimer's disease, severe deficits are present in this cognitive process [27,28]. It is believed that episodic memory is mediated by the circuity of the medial temporal lobe, including the hippocampus, which interacts with other cortical and subcortical structures [29].…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis has shown that episodic memory requires the involvement of multi-brain networks ( Liang et al, 2022 ). DMN and CEN, as the two core networks for maintaining cognition, also play an important role in episodic memory.…”
Section: Discussionmentioning
confidence: 99%